Impact of Yoga in Dental Practice - Karishma Rathore1, Debasruti Naik2, Sthitaprajna Lenka3, Gatha Mohanty4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Dentistry is perceived as a profession that is more stressful than other jobs. Many occupational healthproblems persist in modern dentistry. It is high time we, the dentists, also inculcate the practice of performingYoga in our daily life regime, to strengthen our muscles of neck, shoulder and back, to save ourselves frommusculoskeletal pains. The “Asana” recommended in the Yoga, specifically for posture-related problemscan be of great help to the dental professionals in managing their day to day muscular discomfort and pain.The need of the hour is just to modify our lifestyle to get the maximum out of our professional and personallife. This review article focus on the importance of yoga in dental practice.